PENGARUH PELAYANAN KESEHATANPASIEN RAWAT JALAN TERHADAP KEPUASAN PASIENRSU AISYIYAH PURWOREJO (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
Health services are a form of health effort that is socio-economic in nature, meaning that it is a business that is social in nature but strives to obtain a financial surplus by managing it professionally and paying attention to economic principles. Improving quality in health services is not only oriented towards quality service processes, but also results in quality health services that are in accordance with patient wishes. Knowing the influence of internal medicine outpatient services on patient satisfaction at RSU Aisyiyah Purworejo. The type of research is quantitative. The population in this study is outpatients from the internal medicine clinic at the Aisyiyah Purworejo General Hospital in Purworejo with a population of 50 people. Data were collected using observation, interview and questionnaire techniques. Data were analyzed using Likert scale analysis techniques, multiple simple regression analysis, determination analysis, F test and t test. The results of the F test obtained F count = 9.351 with p = 0.000. Because the p-value < level of significance 0.05. then Ho is rejected and Ha is accepted. This means that there is an influence of the quality of outpatient services on patient satisfaction simultaneously. t test obtained all p-values of the independent variables below 0.05, meaning that each independent variable which includes Tangible, Reliability, Responsiveness, Emphaty and Assurance has a significant influence on outpatient satisfaction at RSU 'Aisyiyah Purworejo. The Adjusted R Square value is 0.460 , this number is called the coefficient of determination value. The determination value is 460 t, meaning that 46.0% of the patient satisfaction level can be explained by service quality which includes tangible aspects, Reliability, Responsiveness, Emphaty and Assurance